Genome-Wide Analysis of CqCrRLK1L and CqRALF Gene Families in Chenopodium quinoa and Their Roles in Salt Stress Response - Jiang, Wei; Li, Chao; Li, Leiting; Li, Yali; Wang, Zhihao; Yu, Feiyu; Yi, Feng; Zhang, Jianhan; Zhu, Jian-Kang; Zhang, Heng; Li, Yan; Zhao, Chunzhao (Frontiers in Plant Science, 2022)
Chenopodium quinoa is a halophyte with exceptional nutritional qualities, and therefore it is potentially an ideal crop to grow in saline soils, not only addressing the problem of land salinization, but also providing nutrient food for the health of humans. Currently, the molecular mechanisms underlying salt tolerance in quinoa are still largely unknown. In Arabidopsis thaliana, Catharanthus roseus receptor-like kinase (CrRLK1Ls) FERONIA (FER) and its ligands rapid alkalinization factors (RALFs) have been reported that participate in the regulation of salt tolerance. Here, we performed a genome-wide analysis and identified 26 CqCrRLK1L and 18 CqRALF family genes in quinoa genome. Transcriptomic profiling of the leaf, root, stamen, and pistil tissues of quinoa reveals that different CqCrRLK1L and CqRALF genes exhibit tissue-specific expression patterns, which is consistent with that observed in other plant species. RNA-seq data show that three CqCrRLK1L genes are highly up-regulated after salt treatment, suggesting that some CqCrRLK1L family genes are transcriptionally responsive to salt stress in quinoa. Biochemical study indicates that CqRALF15, a paralog of Arabidopsis RALF22, is physically associated with CrRLK1L proteins CqFER and AtFER. CqRALF15 and AtRALF22 are functionally conserved in inducing the internalization of AtFER and in triggering root growth inhibition in both quinoa and Arabidopsis. Moreover, overexpression of CqRALF15 in Arabidopsis results in enhanced leaf bleaching under salt stress, indicating that CqRALF15 is involved in salt stress response. Together, our study characterizes CqCrRLK1L and CqRALF family genes in quinoa at genomic, transcriptional, and protein levels, and provides evidence to support their roles in salt stress response.